Communication Strategies of Warning in Novel Jane Eyre by Charlotte Bronte - Fadlul Rahman; Santi Kurniati (JURNAL ARBITRER, 2021)
Jane Eyre's novel was published in 1847 written by (Charlotte, 1983), in the early years of the Victorian period. This research sample is all of the communication strategies of warning that find in the novel Jane Eyre. It can be informed of dialogue between characters or inform of phrases and words related to politeness and communication strategies (Brown & Levinson, 1987). The results show that each character of Jane Eyre can be different from one to another in delivering a warning statement. They tend to give greetings before warning their addressee to respect the addressee, give information or advice toward the addressee, or impose the addressee with a threatening word. Based on basis finding data from 65 forms of speech acts of warning, it is concluded that Brown and Levinson's communication strategies exist in the way of characters' communication in warning their hearer. The strategies are classified into four strategies; bald on the record appear 8 times or 12,3%, positive politeness appears 32 times or 46,2%, negative politeness appears 18 times or 28,6%, and off the record appear 7 times 10,7%. Positive politeness strategy is the most frequent strategy used by characters with the elaboration of several sub-strategies. The sub- strategy most often used is to give reason 7 times or 10.7%.